Bortezomib therapy‐related lung disease in Japanese patients with multiple myeloma: Incidence, mortality and clinical characterization. Issue 2 (21st January 2014) - Yoshizawa, Kazutake; Mukai, Harumi Y.; Miyazawa, Michiko; Miyao, Makiko; Ogawa, Yoshimasa; Ohyashiki, Kazuma; Katoh, Takao; Kusumoto, Masahiko; Gemma, Akihiko; Sakai, Fumikazu; Sugiyama, Yukihiko; Hatake, Kiyohiko; et al.
Abstract : Because of the potentially high mortality rate (6.5%) associated with bortezomib‐induced lung disease (BILD) in Japanese patients with relapsed or refractory multiple myeloma, we evaluated the incidence, mortality and clinical features of BILD in a Japanese population. This study was conducted under the Risk Minimization Action Plan (RMAP), which was collaboratively developed by the pharmaceutical industry and public health authority. The RMAP consisted of an intensive dissemination of risk information and a recommended countermeasure to health‐care professionals. All patients treated with bortezomib were consecutively registered in the study within 1 year and monitored for emerging BILD. Of the 1010 patients registered, 45 (4.5%) developed BILD, 5 (0.50%) of whom had fatal cases. The median time to BILD onset from the first bortezomib dose was 14.5 days, and most of the patients responded well to corticosteroid therapy. A retrospective review by the Lung Injury Medical Expert Panel revealed that the types with capillary leak syndrome and hypoxia without infiltrative shadows were uniquely and frequently observed in patients with BILD compared with those with conditions associated with other molecular‐targeted anticancer drugs. The incidence rate of BILD in Japan remains high compared with that reported in other countries, but the incidence and mortality rates are lower than expected before the introduction of bortezomib in Japan. This study describes the radiographic pattern and clinical characterization of BILD in the Japanese population. The RMAP seemed clinically effective in minimizing the BILD risk among our Japanese population. Abstract : Bortezomib therapy‐related lung disease in Japanese patients with multiple myeloma: Incidence, mortality, and clinical characterization (radiographic pattern).